2019
DOI: 10.1177/0144739418822133
|View full text |Cite
|
Sign up to set email alerts
|

Creating epistemic access through a scaffold approach: Academic literacy skills development for South African first-year public administration students

Abstract: For higher education institutions to produce graduates capable of contributing to society and the economy in a productive manner, educational emphasis is placed on the development of critical thinking. The above necessitates that higher education institutions are able to engage in responsive curriculum design and delivery for enhanced student success and access. Public Administration programmes focus on equipping students to work within the broader government sector, able and capable of delivering public funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…More specifically, this study showed support for scaffolded learning that builds confidence within students, which is consistent with studies such as van Dijk et al (2019) . At a program level, program leaders often ensure learning is scaffolded, typically using pre-requisites.…”
Section: Discussionsupporting
confidence: 89%
“…More specifically, this study showed support for scaffolded learning that builds confidence within students, which is consistent with studies such as van Dijk et al (2019) . At a program level, program leaders often ensure learning is scaffolded, typically using pre-requisites.…”
Section: Discussionsupporting
confidence: 89%
“…Its primary goal is to ensure the efficient and effective functioning of government institutions and the delivery of essential services to the citizens (Gowd, 2022). Public Administration plays a pivotal role in shaping Population Literacy Awareness (Döring, 2021;Döring & Madsen, 2022;van Dijk et al, 2019). Government agencies shoulder the responsibility of disseminating accurate and comprehensible information regarding policies, services, and societal matters (Madathil et al, 2014).…”
Section: Public Administration Population Literacy Awareness Public S...mentioning
confidence: 99%
“…Support was provided by scaffolding content whereby the different tasks of the project were supported separately. According to Hammond and Gibbons (2005), scaffolding refers to the support provided to students to successfully carry out their task at different stages of the task (Van Dijk et al, 2019). This provides guidance for students giving "temporary, responsive support that enables a student to engage with a task that she or he would not otherwise be able to complete" (Calder, 2015(Calder, : 1122.…”
Section: Scaffoldingmentioning
confidence: 99%